J Veterina Sci Res 2019
DOI: 10.36811/jvsr.2019.110005
|View full text |Cite
|
Sign up to set email alerts
|

Baseline survey of Ixodid Ticks Infesting Cattle in Northern State, Sudan

Abstract: Background and objective: Ixodid ticks are serious obstacle to development and utilization of animal resource in tropical countries like Sudan. Over 70 species of tick are prevalent in the Sudan in diverse ecological zones. The aim of this study was to provide a baseline data on tick species infesting cattle in the Northern State, Sudan as a prerequisite to design tick control policy in the state as well as the whole country. Materials and Methods: This study was conducted in April 2017 and included seven pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These studies reported 70 tick species, including Hyalomma anatolicum, H. impressum, H. dromedarii, H. impeltatum, H. rufipes, H. truncatum, Rhipicephalus evertsi evertsi, R. sanguineus, R. praetextatus, R. annulatus, R. decoloratus, Amblyomma lepidum, and Am. variegatum, as the most prevalent tick species in the country [7][8][9][10][11][12][13][14][15][16]. As mentioned, ticks are very important disease vectors for livestock in Sudan; however, owing to the limited resources to perform molecular-based surveys, very few reports on the molecular identification of ticks, with data on only R. sanguineus, are available [14].…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported 70 tick species, including Hyalomma anatolicum, H. impressum, H. dromedarii, H. impeltatum, H. rufipes, H. truncatum, Rhipicephalus evertsi evertsi, R. sanguineus, R. praetextatus, R. annulatus, R. decoloratus, Amblyomma lepidum, and Am. variegatum, as the most prevalent tick species in the country [7][8][9][10][11][12][13][14][15][16]. As mentioned, ticks are very important disease vectors for livestock in Sudan; however, owing to the limited resources to perform molecular-based surveys, very few reports on the molecular identification of ticks, with data on only R. sanguineus, are available [14].…”
Section: Introductionmentioning
confidence: 99%